Boko Haram Jihad Claim in Nigeria and the Sanctity of Life and Property in Islamic law - AbdulHameed Badmas Yusuf (IJUS | International Journal of Umranic Studies, 2022)
Like many countries, Nigeria faces serious acute security challenges due to heinous activities of the deadly group known as Boko Haram (lit. Western Education is Prohibited (Haram)). Right from her emergence till date, this militant group has been terrorizing lives and properties of innocent citizens of the country under the guise of Jihad. But, this jihad claim is baseless in the light of the group’s wanton violation of life and property, the two of the five necessary human interests (maqāsid daruriyyah) which the Shari’ah seeks to protect. Therefore, this paper studies the Boko Haram Jihad claim viz-a-viz her wanton violation of life and property which are regarded by the Islamic law as inalienable human rights as underscored in the theory of maqāṣid al-sharīʿah (Objectives of Shari’ah). Relevant materials were consulted in libraries to carry out the research. Inter alia, it becomes clear from the findings that the concept of Jihad is a sacred duty in Islam, but it has been abused by Boko Haram as evident in her unjustifiable violation of life and property of innocent citizens. This is against the principles of the Qur‘an and the Sunnah, which the group always claims to defend. The paper argues that, while Jihad is sanctioned in Islam, it is guided by rules and regulations. Because life and property are sacrosanct in Islam and nothing can justify their violation as being perpetrated by Boko Haram in Nigeria. Hence, the group’s jihad claim is far from the truth because her activities contradict the lofty objectives of Islamic law (maqāṣid al-sharīʿah) which seek to protect life and property etc. The paper recommends that groups and individuals must have proper understanding of Islam in order to propagate it correctly. Otherwise, the religion of peace would be mistaken for violence and terrorism. Also, the government of Nigeria should ensure fair hearing and justice in dealing with any insurgent groups. This is necessary in view of unfortunate extra-judicial killing of the Boko Haram leader which turned out to be a seed of violence in the northern part of the country.